Waste Treatment Management for Shores and Ocean Cleanness in Pari Island, Indonesia - FRANS ASSA, ADRIE; WIBISONO, CHABLULLAH (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The problem of waste due to domestic and tourism activities in Pari Island is a problem that has not been resolved until now. This study aims to discover how to improve waste treatment management by the community and how to improve waste treatment management by the government in Pari Island Kepulauan Seribu, North Jakarta. Research results show that participation by local communities might involve separating waste at the household level, but the role of the government to provide facilities and infrastructure for transporting waste from the island to the mainland is still very low.RESUMEN El problema de los desechos debido a las actividades domésticas y turísticas en la isla de Pari es un problema que no se ha resuelto hasta ahora. Este estudio tiene como objetivo descubrir cómo mejorar la gestión del tratamiento de residuos por parte de la comunidad y cómo mejorar la gestión del tratamiento de residuos por parte del gobierno en la isla de Pari Kepulauan Seribu, en el norte de Yakarta. Los resultados de la investigación muestran que la participación de las comunidades locales podría implicar la separación de los desechos a nivel de los hogares, pero el papel del gobierno para proporcionar instalaciones e infraestructura para transportar los desechos desde la isla hasta el continente aún es muy bajo.